Textiles Entwerfen in Serie Nahtlosigkeit als Gestaltungsprinzip bei der Hanro AG 1884-1991 - Häsler, Leonie (Reimer Verlag, 2022)
Seamlessness as a design principle: Using the example of the former Swiss textile factory "Hanro," Leonie Häsler describes how fashion was made and clothing produced in the industry. In doing so, she examines the relationships between design, the knitting machine, series production, marketing, and finally musealization.